Shakespeare’s Political Wisdom - Burns, T. author. aut Link
X, 234 p.
Keywords: Shakespeare's Political Wisdom offers interpretations of five Shakespearean plays with a view to the enduring guidance those plays can provide to human, political life. The plays have been chosen for their relentless attention to the questions that were once and may sometime become, or be recognized as being, the heart and soul of politics.